2019
DOI: 10.1002/mawe.201800090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carnauba wax as a part of feedstock on the mechanical behavior of a part made of 4605 low alloy steel powder using metal injection molding

Abstract: Metal injection molding is a growing technology for producing complex metallic components. Preparation of feedstock for metal injection molding is a very crucial step during this process. This is because the deficiencies in quality of the feedstock once made, cannot be corrected by subsequent processing steps. One of the challenges in producing the feedstock is its formulation. In this study, the effect of the percentage of carnauba wax along with other binder constituents of paraffin wax, polypropylene and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The mixing torque is the feedback of energy consumed by the powder dispersed in the adhesive, indicating the viscosity of the mixture. Therefore, evaluating the critical powder loading by monitoring the torque variation during the feedstock mixing is a conventional method [ 33 , 34 ]. The variation of mixing torque with powder loading of feedstock is shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The mixing torque is the feedback of energy consumed by the powder dispersed in the adhesive, indicating the viscosity of the mixture. Therefore, evaluating the critical powder loading by monitoring the torque variation during the feedstock mixing is a conventional method [ 33 , 34 ]. The variation of mixing torque with powder loading of feedstock is shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, finer powders have been used for ceramics, making it more challenging to use backbones in most cases of this process. CW, a natural wax formed on Brazilian palm leaves, can play an essential role in developing proper binder systems for LPIM due to its great potential in particle wetting, gradual division of the debinding process, and lubrication [5,120]. According to the melting temperature, degradation behavior, and viscosity, CW could be a reliable alternative for the backbone in LPIM because it helps to retain the shape during thermal debinding.…”
Section: Binder Systemmentioning
confidence: 99%
“…Powder injection molding (PIM) is a manufacturing technology used to create smallto-medium-sized, highly complicated geometric components with remarkable dimensional and high precision at high production volumes [1][2][3][4]. This process comprises metal injection molding (MIM) and ceramic injection molding (CIM) [5] and uses metal or ceramic powder and polymer binder as raw materials. Binder systems are polymer-based multicomponent mixtures that play a crucial role in the manufacturing and defining of the PIM-produced products' final qualities [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Carnauba wax (CW), a natural wax formed on Brazilian palm leaves, acts as a lubricant and mould releasing agent inside the feedstock. It also helps in particle wetting and gradual division of the debinding process [12][13][14]. This material is an important part of the binder system in many CIM (Ceramic Injection Moulding) and MIM feedstocks [15].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, CW has also been used as a backbone polymer. This is due to the high degradation range of this wax [14]. It has been shown that the percentage of CW has a direct relation with the mechanical properties of the final MIM compact till a certain point after which with the increase in the percentage of CW, the mechanical properties start to decrease [16].…”
Section: Introductionmentioning
confidence: 99%